Efektifitas Ekstrak Bunga Pepaya (Carica papaya) sebagai Bioinsektisida terhadap Kematian Lalat di TPA Ganet, Kota Tanjungpinang - Iwan Iskandar; Hevi Horiza; Saiful Bahri (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
Flies are insect vectors of several types of diseases for humans, such as diarrhea. The number of diarrheal disease sufferers in Tanjungpinang City in 2016 was 2.868. One of flies controlling method is by using bioinsecticide made from papaya (Carica papaya) flower which contains secondary metabolites such as flavonoids, tannins and steroids-triterpenoids. This post-test only designed pre-experiment study was aimed to determine the effectiveness of papaya flower extract as a bio-insecticide against the number of fly deaths. The data were analyzed with one way anova test at 95% confidence level. The number of flies as the study object were 270, which were allocated equally to three dfferent concentration of the papaya flower (25%, 50% and 75%) i.e. each contained 30 flies and repeated three times. The results show that the lowest percen-tage of flies deaths was 76.67% (23 flies) at concentration of 25%, and the highest was 96.67% (28 flies) at concentration of 75%. The results of the one way anova test obtained a p-value less than 0,001. Therefore, it can be concluded that papaya flower extract is effective as bioinsecti-cide for flies.